The Faith, Activity, and Nutrition (FAN) Dissemination and Implementation Study, Phase 1: Implementation Monitoring Methods and Results. (June 2019) - Saunders, Ruth P.; Wilcox, Sara; Jake-Schoffman, Danielle E.; Kinnard, Deborah; Hutto, Brent; Forthofer, Melinda; Kaczynski, Andrew T.
Faith-based settings offer opportunities for reaching populations at risk for chronic conditions and are optimal settings for dissemination and implementation (D&I) research. Faith, Activity, and Nutrition (FAN) is an evidence-based program designed to promote physical activity (PA) and healthy eating (HE) through church policy, systems, and environmental change. We report implementation fidelity for Phase 1 of the FAN D&I project, a countywide effort. The group randomized study included pre- and postintervention assessments of core PA and HE components. We compared implementation in early intervention ( n = 35) versus delayed intervention (control, n = 19) churches; assessed individual church implementation; and examined the effects of level of implementation on church member outcomes. Implementation assessments were conducted with the FAN coordinator via telephone survey. Study outcomes were assessed with church members 8 to 12 months following baseline assessment via self-administered surveys. We found significantly higher levels of implementation for PA opportunities, PA and HE guidelines, PA and HE messages, and PA and HE pastor support in intervention versus control churches and showed church-level variation in PA and HE implementation. PA self-efficacy varied by level of implementation; high and low implementers did not differ in proportion of church members physically inactive, although low implementers had fewer members inactive than controls. The high level of implementation in intervention churches shows promise for broader dissemination of FAN.